Báo cáo sự cố tàu Trung Quốc cắt cáp thu địa chấn của tàu Bình Minh 02 ngày 26/05/2011 - Petro Việt Nam (2011)
Báo cáo sự cố tàu Trung Quốc cắt cáp thu địa chấn của tàu Bình Minh 02 vào lúc 5h58'' ngày 26/5/2011